Pick‐and‐Place Assembly of Single Microtubules. Issue 32 (10th July 2017) - Tarhan, Mehmet Cagatay; Yokokawa, Ryuji; Jalabert, Laurent; Collard, Dominique; Fujita, Hiroyuki
Abstract : Intracellular transport is affected by the filament network in the densely packed cytoplasm. Biophysical studies focusing on intracellular transport based on microtubule–kinesin system frequently use in vitro motility assays, which are performed either on individual microtubules or on random (or simple) microtubule networks. Assembling intricate networks with high flexibility requires the manipulation of 25 nm diameter microtubules individually, which can be achieved through the use of pick‐and‐place assembly. Although widely used to assemble tiny objects, pick‐and‐place is not a common practice for the manipulation of biological materials. Using the high‐level handling capabilities of microelectromechanical systems (MEMS) technology, tweezers are designed and fabricated to pick and place single microtubule filaments. Repeated picking and placing cycles provide a multilayered and multidirectional microtubule network even for different surface topographies. On‐demand assembly of microtubules forms crossings at desired angles for biophysical studies as well as complex networks that can be used as nanotransport systems. Abstract : Pick‐and‐place assembly of single microtubule filaments is reported. A multilayered and multidirectional microtubule network can be generated using MEMS tweezers even for different surface topographies. Assembly based on the microtubule polarity is achieved to develop motor protein‐based transport systems or to investigate intracellular transport along intersecting microtubules.